One Program Fits All? Patterns and Outcomes of Professional Development During a Large-Scale Reform in a High-Stakes Science Curriculum. (July 2021) - Hübner, Nicolas; Fischer, Christian; Fishman, Barry; Lawrenz, Frances; Eisenkraft, Arthur
When translating large-scale policy changes into educational practice, classroom-level implementation is crucial and dependent on teachers' capabilities. Most research underscores the importance of professional development (PD) as a proximal factor to achieve educational change. Connected to the recent Advanced Placement (AP) science examination reform, this large-scale quantitative study (NTeachers = 9, 096; NStudents = 197, 589) investigates teacher participation in different PD formats (i.e., face-to-face, online, materials) and their associations with teacher- and student-level outcomes. We found that teacher characteristics (e.g., gender and administrative support) were associated with the choice of the PD format. We also found AP subscore differences between students of teachers who participated in different PD formats. Furthermore, teachers who participated in formal PD activities tended to report higher challenges with the AP reform. Thus, this study encourages PD providers to implement changes alongside a variety of PD programs to account for the potential differential benefits for teachers.